Interaction Between Florfenicol and Doxycycline Involving Cytochrome P450 3A in Goats (Capra hricus) - Wang, Xiaojing; Yang, Yaqin; Martínez, María-Aránzazu; Martínez, Marta; Lopez-Torres, Bernardo; Martínez-Larrañaga, María-Rosa; Wang, Xu; Anadón, Arturo; Ares, Irma (Frontiers in Veterinary Science, 2021)
When two drugs are combined, drug-drug interactions (DDI) often occur. Metabolic DDI usually occur due to inhibition of the metabolism of one drug by the other. This leads to an increase in the plasma concentration of the drug whose metabolism is inhibited. The objective of this research study was to verify the DDI risk of two antibacterial, florfenicol (FF) and doxycycline (DOX) due to metabolism. Because food containing residues of any pharmacologically active substance could potentially constitute a public health hazard, we selected a food producing animal, goat, goat liver microsomes and recombinant metabolic enzymes, for in vivo and in vitro metabolism studies. In vitro experiments showed that CYP3A was the key enzyme subfamily in FF metabolism, DOX slowed down FF metabolism and R440 was possibly the key amino acid in the metabolic interaction between FF and DOX. In vivo studies in the goats showed that DOX inhibited up-regulation of CYP3A24 gene expression produced by FF; in liver and kidney, DOX slightly slowed down FF metabolism. Quantitative prediction of DDI risk suggest that when DOX is used in combination with FF in veterinary medicine, may result in a clinical significant increase of FF plasma and tissue concentrations, resulting a prevalence of harmful tissue residues of medicinal products in the food chain. Through our experimentation, when DOX is used in combination with FF, the withdrawal time of FF in the kidney was extended by 1 day. Otherwise, an appropriate withdrawal time (20 days) of FF was established for FF and DOX combined use to ensure that the animal can be safely slaughtered for food.